Women at work: work family conflict and well being - Sandhu, Sarvinder Kaur (Universiti Putra Malaysia Press, 2008)
Many women have diverted from their traditional single role as home makers who are financially dependent on their husbands to the double roles of being home makers and wage earners. In fitting into their second role as wage earners, women are often confronted with their main challenge of balancing work and family. This study looked into the work conditions of employed women, namely time at work, workload, conflicts at work, and the lack of support at work, as well as family conditions such as the number of children, presence of young children and lack of support at home, and work-family conflict. This study determined the effects of the predictors on employed women’s well-being. The participants of this study were limited to women secretaries/clerks who are married with children in the Klang Valley. The research was conducted using the survey method of questionnaire and the data was analysed using the SPSS (Statistical Package for the Social Sciences). In conclusion, this study found that the above mentioned predictors, namely work conditions, family conditions and work-family conflict did affect employed women’s well-being; these predictors affected them in different ways including psychological distress, physical health symptoms and low job satisfaction.